Refugees’ post-arrival and displacement-related perceptions in Malaysia and Portugal - Tai, L.L.; Guerra, R.; Bierwiaczonek, K. (Globalization in context: Proceedings from the 27th Congress of the International Association for Cross-Cultural Psychology Conferences, 2025)
Countries receiving refugees can vary dramatically in their policies toward this group (e.g., recognition of refugee status, legal protections), but the role of the receiving country context for refugee adaptation process is under investigated. This cross-sectional study (N = 318) investigates refugees’ perceptions of the forcedness of their displacement and perils related to it, perceived discrimination, and subjective well-being in two different country contexts: Portugal and Malaysia. Results showed perceptions of discrimination and displacement-related perils were significantly higher among refugees in Malaysia, while subjective well-being and perceptions of forcedness were significantly higher for refugees in Portugal. For both groups, perceived discrimination and perceptions of forcedness had a significant and negative relation with subjective well-being but were not associated with related perils. In contrast to theoretical predictions, perceptions of forcedness, related perils and country-context did not moderate the relationship between perceived discrimination and subjective well-being. We propose that the differences between refugees in Malaysia and Portugal are a product of specific social and political factors. Limitations, practical implications, and future research avenues are discussed.